Prevalence of Enterococcus Species and their Antibiogram in a Tertiary Care Hospital of Gandaki Province, Nepal (Med Phoenix, 2025)
Introduction: Enterococcus species, part of the normal intestinal flora, have emerged as significant pathogens causing healthcare-associated infections worldwide. Their intrinsic and acquired resistance to multiple antibiotics, including last-resort agents, poses therapeutic challenges, especially in low-resource settings such as Nepal. However, data on their prevalence and resistance patterns in Gandaki Province are scarce. The aim of the study is to determine the prevalence of Enterococcus species in clinical samples and evaluate their antimicrobial susceptibility patterns in a tertiary care hospital in Gandaki Province, Nepal.Materials and methods: A descriptive cross-sectional study was conducted from October 2024 to March 2025 at the Department of Microbiology, Western Regional Hospital, Pokhara Academy of Health Sciences. Ninety-three Enterococcus isolates were recovered from various clinical specimens. Species identification and antibiotic susceptibility testing were performed using standard microbiological methods and the Kirby-Bauer disk diffusion technique following CLSI guidelines.Results: Enterococcus faecalis was the predominant species (93.5%), followed by E. faecium (6.5%). Both species showed 100% susceptibility to vancomycin. High resistance was noted against penicillin, ciprofloxacin, and ampicillin. E. faecalis exhibited high sensitivity to linezolid, teicoplanin, and nitrofurantoin, while E. faecium showed considerable resistance to penicillin and HLG but remained fully sensitive to vancomycin, linezolid, and nitrofurantoin.Conclusion: E. faecalis is the most common Enterococcus species in clinical samples from Gandaki Province, with notable resistance to commonly used antibiotics. Continuous antimicrobial resistance surveillance and targeted stewardship interventions are essential to optimize treatment and control multidrug-resistant Enterococcus infections. We recommend strengthening antimicrobial stewardship programs and ongoing surveillance to monitor resistance trends and guide effective therapy against Enterococcus infections.